2015
DOI: 10.1074/jbc.m115.655654
|View full text |Cite
|
Sign up to set email alerts
|

Structural Hot Spots Determine Functional Diversity of the Candida glabrata Epithelial Adhesin Family

Abstract: Background:The pathogenic yeast Candida glabrata harbors more than 20 epithelial adhesins (Epas). Results: Epas are lectins with binding pockets that contain conserved and variable structural features determining ligand binding affinity and specificity. Conclusion: The functionally diverse Epa family evolved in C. glabrata for efficient host infection. Significance: Epa-mediated host-ligand binding is a therapeutic target to combat C. glabrata infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 54 publications
1
66
0
Order By: Relevance
“…Briefly, all DSY562 CDS were screened with the help of the software FungalRV which helps to predict the occurrence of adhesin-like proteins in fungal genomes (Chaudhuri et al 2011). We next analysed the list of potential adhesins for occurrence of PFAM domains and the presence of specific signatures including i) the presence of signal peptides and absence of internal transmembrane domains, ii) the presence of consensus sequence for GPI anchor, iii) the presence of AWP motifs (de Groot et al 2013); iv) the presence of motifs typical for the class of EPA proteins following (Diderrich et al 2015) and (Gabaldón et al 2013), v) the presence of PIR motifs and lastly iv) the occurrence of hyphally-regulated cell wall proteins (Hyphal_reg_CWP, IPR021031). For practical reasons and for comparison purposes with CBS138, we used the same CAGL0 gene naming that is currently accepted for CBS138.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, all DSY562 CDS were screened with the help of the software FungalRV which helps to predict the occurrence of adhesin-like proteins in fungal genomes (Chaudhuri et al 2011). We next analysed the list of potential adhesins for occurrence of PFAM domains and the presence of specific signatures including i) the presence of signal peptides and absence of internal transmembrane domains, ii) the presence of consensus sequence for GPI anchor, iii) the presence of AWP motifs (de Groot et al 2013); iv) the presence of motifs typical for the class of EPA proteins following (Diderrich et al 2015) and (Gabaldón et al 2013), v) the presence of PIR motifs and lastly iv) the occurrence of hyphally-regulated cell wall proteins (Hyphal_reg_CWP, IPR021031). For practical reasons and for comparison purposes with CBS138, we used the same CAGL0 gene naming that is currently accepted for CBS138.…”
Section: Resultsmentioning
confidence: 99%
“…The list of potential adhesins was further subjected to several additional tests including a search for PFAM domains (http://pfam.xfam.org/search#tabview=tab1) and the presence of specific signatures relevant for the detection of adhesin-like proteins. These signature included i) the presence of signal peptides and absence of internal transmembrane domains using the online programs SignalP and TMHMM (http://www.cbs.dtu.dk/services/), ii) the presence of consensus sequence for GPI anchor ([NSGDAC] – [GASVIETKDLF] – [GASV] – X(4,19) – [FILMVAGPSTCYWNQ](10)>) as recommended by (Weig et al 2004), iii) the presence of AWP motifs (VSHITT) (de Groot et al 2013); iv) the presence of EPA motifs (EPA CC: CX(27)CX(40)CX(44)DDX(13)CC) and EPA: GCSX(8,9)GL) following (Diderrich et al 2015) and(Gabaldón et al 2013); v) the presence of PIR motifs (Q[IV]XDGQ[IVP]Q) following (de Groot et al 2008).…”
Section: Methodsmentioning
confidence: 99%
“…The list of potential adhesins was further subjected to several additional tests including a search for PFAM domains ( http://pfam.xfam.org/search#tabview=tab1 ) and the presence of specific signatures relevant to the detection of adhesin-like proteins. These signature included (i) the presence of signal peptides and absence of internal transmembrane domains using the online programs SignalP and TMHMM ( http://www.cbs.dtu.dk/services/ ); (ii) the presence of consensus sequence for GPI anchor ([NSGDAC] – [GASVIETKDLF] – [GASV] – X(4,19) – [FILMVAGPSTCYWNQ](10)>), as recommended by Weig et al (2004) ; (iii) the presence of AWP motifs (VSHITT) ( de Groot et al 2013 ); (iv) the presence of EPA motifs (EPA CC: CX(27)CX(40)CX(44)DDX(13)CC) and EPA: GCSX(8,9)GL) following Diderrich et al (2015) and Gabaldón et al (2013) ; and (v) the presence of PIR motifs (Q[IV]XDGQ[IVP]Q) following ( de Groot et al 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of the intestinal tract, a previous study identified adhesion properties of specific adhesins of C. glabrata expressed in S. cerevisiae to human epithelial colorectal adenocarcinoma cells (Caco2). The authors found that the adhesive properties of different adhesins ranged from significant to very weak adherence with Epa1, 6, and 7 displaying significant to moderate adhesion and Epa19-21 displaying weak adhesion [106]. C. glabrata colonization of the gastrointestinal tract is not well understood.…”
Section: Adhesionmentioning
confidence: 99%